Demonstration of measuring sea fog with an SNSPD-based Lidar system. Issue 1 (December 2017) - Zhu, Jiang; Chen, Yajun; Zhang, Labao; Jia, Xiaoqing; Feng, Zhijun; Wu, Ganhua; Yan, Xiachao; Zhai, Jiquan; Wu, Yang; Chen, Qi; Zhou, Xiaoying; Wang, Zhizhong; et al.
Abstract The monitor of sea fogs become more important with the rapid development of marine activities. Remote sensing through laser is an effective tool for monitoring sea fogs, but still challengeable for large distance. We demonstrated a Long-distance Lidar for sea fog with superconducting nanowire single-photon detector (SNSPD), which extended the ranging area to a 180-km diameter area. The system, which was verified by using a benchmark distance measurement of a known island, is applied to the Mie scattering weather prediction Lidar system. The fog echo signal distribution in the range of 42.3∼63.5 km and 53.2∼74.2 km was obtained by the Lidar system. Then the fog concentration and the velocity of the fog were deduced from the distribution, which is consistent with the weather prediction. The height of the sea fog is about two hundred meter while the visibility at this height is about 90 km due to the Earth's radius of curvature. Therefore, the capability of this SNSPD-based Lidar was close to the theoretical limit for sea fog measurements for extremely high signal-to-noise ratio of SNSPD.